The Effect Of Compensation On Employee Work Motivation Of Koperasi Karyawan PDAM Sidoarjo - Damarsari Ratnasahara Elisabeth; Joko Suyono; Akhmad Nasir (IJEBD International Journal Of Entrepreneurship And Business Development eISSN 2597-4785 pISSN 2597-4750)
The object of research is Koperasi Karyawan PDAM (Drinking Water Company) Sidoarjo. This type of research is quantitative, the objective of this research is to measure the influence of independent variables and their contribution to the dependent variable, the independent variable is compensation which consist of direct compensation and indirect compensation and the dependent variable is employee motivation. Among the two independent variables, it turns out that both of them have a significant effect on employee work motivation of Koperasi Karyawan PDAM Sidoarjo. Both simultaneously and partially proved to be significant, meaning that both independent variables contributed to employee motivation.